The Mayor of Batam Ex-Officio as Head of The Batam Concession Agency: Cross-Jurisdictional Authority and Legal Problems - Soerya Respationo (Faculty of Law, Universitas Pekalongan, 2024)
This research aims to explore the impact of granting the position of Head of the Batam Concession Agency to the Mayor of Batam on an ex-officio basis on the principle of